Mental health service delivery in rural Nepal: opportunities and challenges with insights from Jumla (Karnali Province) - Poudel, Siddhartha; Parajuli, Apekshya; Saud, Dhruba; Sharma, Pratikshya; Acharya, Roshan (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Mental disorders are among the leading contributors to Nepal’s disease burden, with depressive and anxiety disorders ranking among the leading causes. However, access to care is grossly unequal. Mental health professionals and services are concentrated in urban centers, whereas rural areas such as Jumla suffer severe shortages of trained providers, medicines, and functional referral systems. Stigma, cultural beliefs, and reliance on traditional healers further delay help seeking from formal services, while many individuals remain untreated even when services do exist. Financial constraints, lack of awareness, and limited health-system capacity widen this treatment gap. Such challenges bring into sharp focus the need to understand barriers to service delivery and to identify feasible, culturally grounded strategies for integrating mental health care within rural primary health systems.Methods: We conducted a narrative synthesis of Nepal-specific literature, implementation reports, and qualitative studies. Sources included published surveys, primary-care evaluations, reviews of stigma and policy, and local JKAHS reports.Results: Promising approaches include supervised task-sharing, culturally tailored community engagement (including partnerships with traditional healers), adaptation of WHO’s mhGAP training, and use of digital decision-support tools. Key recommendations for Jumla include reinforcing health-system supports (reliable medication supply, private counseling space, referral networks), piloting offline-capable e-mhGAP apps, and engaging community stakeholders (FCHVs, local leaders, healers) in co-designing stigma reduction and referral programs. Evidence from Jumla’s recent mental-health conference and local studies underscores readiness for integrated models.Conclusion: Implementation research and monitoring are needed to ensure the feasibility, acceptability, and effectiveness of these interventions in Karnali.